2015
DOI: 10.1242/jcs.163030
|View full text |Cite
|
Sign up to set email alerts
|

Endocytic deficiency induced by intersectin-1s knockdown alters the Smad2/3-Erk1/2 signaling balance downstream of Alk5

Abstract: Recently, we demonstrated in cultured endothelial cells and in vivo that deficiency of an isoform of intersectin-1, ITSN-1s, impairs caveolae and clathrin-mediated endocytosis and functionally upregulates compensatory pathways and their morphological carriers (i.e. enlarged endocytic structures, membranous rings or tubules) that are normally underrepresented. We now show that these endocytic structures internalize the broadly expressed transforming growth factor β receptor I (TGFβ-RI or TGFBR1), also known as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(45 citation statements)
references
References 80 publications
4
41
0
Order By: Relevance
“…Since ITSN and Grb2 compete for Sos [14], reduced levels of ITSN in cells may increase Sos availability for Grb2, favoring the Alk5-Sos1-Grb2 pathway over the Alk5-Smad-SARA route. Studies in knockdown ITSN1-S mouse lungs demonstrate a preference for the Alk5-Sos1-Grb2 pathway leading to persistent activation of ERK1/2 and the proliferation of pulmonary endothelial cells [55]. These findings suggest that ITSN attenuates Ras-ERK activation by the TGFβ pathway in contrast to previous work suggesting that ITSN promotes Ras activation [50, 59].…”
Section: Functionmentioning
confidence: 90%
See 2 more Smart Citations
“…Since ITSN and Grb2 compete for Sos [14], reduced levels of ITSN in cells may increase Sos availability for Grb2, favoring the Alk5-Sos1-Grb2 pathway over the Alk5-Smad-SARA route. Studies in knockdown ITSN1-S mouse lungs demonstrate a preference for the Alk5-Sos1-Grb2 pathway leading to persistent activation of ERK1/2 and the proliferation of pulmonary endothelial cells [55]. These findings suggest that ITSN attenuates Ras-ERK activation by the TGFβ pathway in contrast to previous work suggesting that ITSN promotes Ras activation [50, 59].…”
Section: Functionmentioning
confidence: 90%
“…The impairment of these pathways leads to the upregulation of alternative pathways that include the presence of enlarged endocytic structures. These endocytic structures internalize the transforming growth factor β (TGFβ) receptor I, also named Alk5, resulting in its degradation [55, 56]. The effects of such degradation are important, since the TGFβ pathway is involved in cell proliferation, differentiation and apoptosis.…”
Section: Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…This interaction could rescue the aberrant phenotype, thereby improving the overall severity of the disease; this mechanism was previously demonstrated in other types of lung disease. 43,44 Although not tested, if true, administering PHD2-containing microparticles of hematopoietic cell origin may prove efficacious in treating idiopathic PAH patients. Regardless, this is the first study, to our knowledge, to generate a severe mouse model of PAH that recapitulates almost all key pathologic features exhibited in the human PAH phenotypes.…”
Section: Egln1 Knockout Micementioning
confidence: 99%
“…2 TGFb has been shown to induce Erk1/2 MAPK signaling in endothelial and epithelial cells, fibroblasts, breast and colorectal cancer to promote disassembly of adherens junctions, cell migration and proliferation. 3,4 Studies to understand the molecular mechanisms underlying TGFb-dependent Erk1/2 MAPK activation indicated that plasma membrane-bound activated Alk5/ TGFbRII heteromer recruits and phosphorylates the adaptor protein ShcA followed by the ShcA/Grb2/mSos complex assembly. 5 Localization of mSos/Grb2 at the plasma membrane level is the primary mechanism for Ras activation.…”
Section: Itsn-1s and Tgfb-mediated Erk1/2 Mapk Signalingmentioning
confidence: 99%